Positive Association between TGFB1 Gene and Susceptibility to Idiopathic Scoliosis in Bulgarian Population. (18th July 2018) - Nikolova, Svetla; Dikova, Milka; Dikov, Dobrin; Djerov, Assen; Savov, Alexey; Kremensky, Ivo; Loukanov, Alexandre
Abstract : Idiopathic scoliosis (IS) is a common medical condition beginning in childhood and characterized by strong evidence for a genetic susceptibility to three-dimensional spinal deformity. The primary goal of the current case-control study is to examine the association between the TGFB1 (-509C/T) functional polymorphic variant and genetic predisposition to IS in the Bulgarian population and the genotype-phenotype correlations in distinct case-control subgroups based on age at onset, family history, and gender. A total of 127 patients with primary scoliosis and 254 gender-matched control subjects were recruited. The mean Cobb angle was 53.8 ± 21.2°. Genotyping of cases and controls was performed using the TaqMan real-time amplification technique. The results were processed statistically using Pearson's Chi-squared test and Fisher's exact test with a value of p less than 0.05 as statistically significant. The polymorphic T allele and TT genotype were associated with a greater incidence of IS and can be considered as predisposing factors with a moderate effect on deformity development. The current results suggested that there was a genetic predisposition in early and late onset IS and familial, sporadic, and female cases. Nevertheless, replication studies are needed to reveal the relationship between the TGFB1 locus and certain subtypes of IS in different populations.